2017
DOI: 10.1080/09658211.2017.1340483
|View full text |Cite
|
Sign up to set email alerts
|

The differential contributions of visual imagery constructs on autobiographical thinking

Abstract: There is a growing theoretical and empirical consensus on the central role of visual imagery in autobiographical memory. However, findings from studies that explore how individual differences in visual imagery are reflected on autobiographical thinking do not present a coherent story. One reason for the mixed findings was suggested to be the treatment of visual imagery as an undifferentiated construct while evidence shows that there is more than one type of visual imagery. The present study investigates the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 79 publications
7
26
1
1
Order By: Relevance
“…Vannucci, Pelagatti, Chiorri, and Mazzoni (2016) showed that-compared to low-object imagersindividuals with strong object imagery were faster to generate autobiographical memories in response to cue phrases and reported more sensory and perceptual details and associated visual images in their memories; but Sheldon, Amaral, and Levine (2017) found that interfering with visual imagery processes impeded recall of event details (particularly spatial ones) more for individuals high in spatial imagery, while its impact did not differ for individuals with differing object imagery abilities. Aydin (2018) found that object imagery was related to AUTOBIOGRAPHICAL EPISODIC MEMORY AND NAVIGATION 15 phenomenological characteristics such as the level of sensory and perceptual details retrieved in relation to past experiences, whereas spatial imagery predicted the level of episodic specificity of past events. Clark et al (2019) reported that navigation performance dissociated from autobiographical memory retrieval and scene construction, and they speculated that navigation reflects schematic, spatial imagery whereas autobiographical memory draws upon vivid imagery for objects and scenes.…”
Section: Discussionmentioning
confidence: 99%
“…Vannucci, Pelagatti, Chiorri, and Mazzoni (2016) showed that-compared to low-object imagersindividuals with strong object imagery were faster to generate autobiographical memories in response to cue phrases and reported more sensory and perceptual details and associated visual images in their memories; but Sheldon, Amaral, and Levine (2017) found that interfering with visual imagery processes impeded recall of event details (particularly spatial ones) more for individuals high in spatial imagery, while its impact did not differ for individuals with differing object imagery abilities. Aydin (2018) found that object imagery was related to AUTOBIOGRAPHICAL EPISODIC MEMORY AND NAVIGATION 15 phenomenological characteristics such as the level of sensory and perceptual details retrieved in relation to past experiences, whereas spatial imagery predicted the level of episodic specificity of past events. Clark et al (2019) reported that navigation performance dissociated from autobiographical memory retrieval and scene construction, and they speculated that navigation reflects schematic, spatial imagery whereas autobiographical memory draws upon vivid imagery for objects and scenes.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association of pre-frontal and frontal lower beta and mid-beta ratios, 16-24 Hz, and parietal lower beta-1, 12 -16 Hz, from EO recordings with more consistent CVS and HRT were demonstrated by the cross-validated neural networks as depicted in Figure 5, but not detected by the multivariate regression models. Although we did not test our participants in terms of having correlates of ADHD, our findings for increased frontal lower beta-2 -which did not appear as significant predictors in the regression models-are in line with the increased parietal beta (13)(14) and frontal beta (17)(18) being associated with lower variability in the CPT scores of ADHD participants [20]. The ADHD was found to be associated with increased cortical activation in the form of decreased theta and increased (lower) beta to compensate for the increased arousal -and weaker slow alpha-during the resting states [20].…”
Section: Opposite Roles Of Beta Sub-bands In Predicting Task Consimentioning
confidence: 61%
“…Furthermore, momentary pauses disrupt the natural tonic levels of sustained attention in otherwise fatigued individuals [12]. Finally, self-reported ratings with the Likert scale ignore the immediate reactions to the stimuli and require reflective thinking and decision making [13] while the parameters used to assess these cognitive variables should not be affected by delay and consequent memory lapses. In more objective assessments, the average number of errors gives a continuous measure for classification of vigilance patterns [14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with this well documented importance of the phenomenological characteristics of ABM, in most published studies the evaluation of phenomenological experiences has been limited to a relatively small number of potentially relevant dimensions. Moreover, only in some studies these dimensions have been measured by standardized instruments, such as the Memory Characteristics Questionnaire (MCQ, Johnson et al , 1988) and the Autobiographical Interview (AI, Levine, Svoboda, Hay, Winocur & Moscovitch, 2002), while in many other instances the assessment has been done by simply creating ad hoc items or by taking single items from existing instruments (e.g., Aydin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies (Aydin, 2018; Vannucci et al , 2016) investigated the relationship between the phenomenology of ABMs and individual differences in visual imagery as a cognitive style. In the study by Vannucci et al (2016) individuals with high levels of object imagery remembered more personal memories and with shorter retrieval times compared to individuals with low levels and they also rated their ABMs as more detailed and mainly recalled as visual images.…”
Section: Introductionmentioning
confidence: 99%